2020
DOI: 10.1177/2150132720945898
|View full text |Cite
|
Sign up to set email alerts
|

Poorer Diet Quality Observed Among US Adults With a Greater Number of Clinical Chronic Disease Risk Factors

Abstract: Background Obesity and chronic disease risk are significantly related to healthy lifestyle behavior, including dietary intakes. Further, the interrelated etiology of many chronic conditions supports the comorbidity in US adults to manage multiple diagnoses. The purpose of this study was to assess diet quality across varying numbers of existing conditions, including obesity, hypercholesterolemia, hyperglycemia, and hypertension. Methods Cross-sectional analysis of data from 17 356 adults aged 45 years and older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 22 publications
1
29
0
2
Order By: Relevance
“…The group averaged a level of weight loss across 16 weeks similar to other DPP trials (e.g., [68]). Consistent with the present study, adults with chronic disease risk factors have poorer quality diets [69]. Employee-based interventions to improve the health of workers in high-stress work environments, such as long-term care, are highly needed, coupled with safety and fully integrated into the workplace [70].…”
Section: Discussionsupporting
confidence: 84%
“…The group averaged a level of weight loss across 16 weeks similar to other DPP trials (e.g., [68]). Consistent with the present study, adults with chronic disease risk factors have poorer quality diets [69]. Employee-based interventions to improve the health of workers in high-stress work environments, such as long-term care, are highly needed, coupled with safety and fully integrated into the workplace [70].…”
Section: Discussionsupporting
confidence: 84%
“…This study found that, with every increase in the standard deviation of TDS (1 SD = 2.19 units of TDS), there was an 8% decrease in risk of all-cause mortality [25]. Further to this, another American study [67] exploring the relationship between four disease risk factors on diet quality found that those with one or none of the clinical risk factors had significantly higher total diet quality score (55.7 out of a possible 100), as measured by the Healthy Eating Index-2015, when compared with those who had all four risk factors. Those with all four risk factors had a significantly lower diet quality score of (51.1).…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, we found that pre-existing hypertension, but not diabetes, was associated with lower HEI-2015 scores. Lower dietary quality is often linked with increased risk of these conditions (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%